EFEKTIVITAS PENGGUNAAN APLIKASI M-TIX DAN TIX ID DALAM PEMBELIAN TIKET BIOSKOP DI KALANGAN MAHASISWA - Fadhilah, Nadiya; Quranisari, Siti Hatifah (Transpublika Publisher, 2022)
This study aims to determine how effective the use of the M-TIX and TIX ID applications in purchasing cinema tickets among students is. The research method used is descriptive qualitative research method and data collection is carried out by survey using a questionnaire via google form. There were as many as 50 students as samples in this study. The results showed that as many as 98% of respondents knew about the M-TIX and TIX ID applications, 100% of respondents agreed that the M-TIX and TIX ID applications were useful to use, and on the effectiveness aspect, 100% of respondents agreed that the M-TIX and TIX applications were useful. TIX ID is effective in purchasing cinema tickets. Hence, it can be concluded that according to students the M-TIX and TIX ID applications are effective for use in purchasing tickets at the cinema.